Impacto da reabilitação cardiorrespiratória precoce e da CPAP no pós-operatório de cirurgia de revascularização do miocárdio - Pantoni, Camila Bianca Falasco (2013)
The thesis consisted of two studies described below. The study I, entitled: " Shortterm exercise-based program promotes better recovery of linear and non-linear analysis of heart rate after off-pump coronary artery bypass surgery- a prospective clinical trial. aimed to investigate changes in heart rate variability (HRV) after coronary artery bypass grafting (CABG) with and without the use of cardiopulmonary bypass (CPB) and the behavior of the cardiac autonomic nervous system (cANS) in patients submitted to the different techniques and to an inpatient rehabilitation program in the postoperative period. The cANS was evaluated by HRV indices in patients undergoing surgery with (n = 30) and without CPB (n = 14) and was obtained in the preoperative period, on the first day of postoperative period (1oPO) and on pre-discharge day. Both groups showed HRV reduction after surgery. The rehabilitation program promoted improvement of linear and nonlinear HRV indices at pre-discharge day for both groups, compared to the 1oPO. However, patients undergoing off-pump surgery presented higher HRV indices in the pre-discharge day, with better recovery of cANS function. Our data suggest that inpatient rehabilitation program applied to patients undergoing CABG without CPB promoted greater cANS adaptations, compared to patients undergoing other operative technique. The second study, also conducted in patients undergoing CABG, was entitled "Impact of physical exercise associated to CPAP application after coronary artery bypass grafting surgery- a randomized controlled trial." aimed to evaluate the impact of continuous positive airway pressure (CPAP) on exercise tolerance, breathing pattern (BP), dyspnea sensation and peripheral oxygen saturation (SpO2) during the first day of ambulation in post-CABG. Twenty-seven patients were randomized to the control group-CG (ambulation in spontaneous breathing) (n = 14) or to CPAP group-CPG (ambulation associated to CPAP between 10-12 cmH2O) (n = 13). The outcomes included BP variables, assessed by respiratory inductive plethysmography (Lifeshirt system), exercise tolerance limit, dyspnea sensation and SpO2. The CPG showed greater exercise tolerance, better thoracoabdominal coordination during rest and exercise, higher SpO2 values at the end of ambulation and less dyspnea sensation compared to CG. Thus, we conclude that CPAP was able to positively impact the BP and exercise capacity of patients in post-CABG. These results may provide a feasible and effective approach for early rehabilitation.